larval rearing of the white leg shrimp Penaeus vannamei and the first culture laboratory in Iraq, Basrah - Ghazi, A.H.; Ali, M. A.; AL-Noor, S. S. (Iraqi Journal of Aquaculture, 2022)
In the study we cultured the shrimp L. vannamei (initial weight 0.0004 g) under laboratory conditions in marine science center and using three types of food. These were life food (Artemia nauplii), artificial died and mixed food (Artemia nauplii and artificial died). The highest average weight were achieved when feeding on the mixed feed (1.210 g), while, lower values achieved when fed on artificial diets 0.220 g. There are significant differences (P<0.05) between these three food types. A similar results were obtained for growth in terms of length, the highest average length of larvae after six weeks was achieved when fed on the mixed food (36.58 mm ), comparing with these larvae fed on Artemia and artificial feed were 31.11 and 18.72 mm respectively, and there are difference significantly too (P < 0.05) between the three food types. The highest average weight increment was recorded during the sixth week with mixed food it was 0.55 g, compared with 0.23g and 0.12 g for Artemia and artificial diets respectively. The higher survival rates after sixth week were calculated for the three treatments, the high survival in larvae fed on Artemia it was 90.58 %, while, these fed on mixed food and artificial diet it was 85.62% and 73.24 % respectively.